RELIABILITY EVALUATION OF COMPOSITE STANDARD BRIDGE USING VEHICULAR WEIGH-IN-MOTION MEASUREMENT DATA - Widi Nugraha; Setyo Hardono (Widyariset, 2015)
The Bina Marga standard bridge has been implemented as bridge designing references in Indonesia. One of the standard bridge types is a composite bridge. This composite bridge is designed based on RSNI T-02-2005, an Indonesian bridge loading standard. This standard is based on Load and Resistance Factored Design (LRFD) method. LRFD method is treating statistical data on loads and strengths as random variables that have to be evaluated periodically using reliability index as the indicator. The purpose of this research is to evaluate the reliability of a 25 m simple span composite bridge structure due to statistical load data from weigh-in-motion (WIM) vehicular loads measurement in Pantura highway of Cikampek-Pamanukan, West Java in 2011 and RSNI T-02-2005 nominal vehicular load. The results of this research are maximum bending moment due to RSNI T-02-2005 nominal vehicular load is 526.55 kNm with a probability of exceedance of 4.5 x 10-7 and the reliability index of this composite bridge is 7.16, which is larger than reliability target of AASHTO of 3.50.